Perancangan UI/UX Layanan Aduan Fasilitas Umum dengan Metode Design Thinking Berbasis Mobile - Khansa, Shafa Salsabila; Rahman, Azka Septia; Ramadhan, Della Novia; Huda, Muhammad Qomarul (Journal of System and Computer Engineering, 2024)
This research examines the UI/UX design for public facility complaint services in South Tangerang City, using the Design Thinking methodology. The primary focus is to meet the needs of users, including complaint submitters and government officials. The prototype created was tested through Maze to collect data related to the application's usage. During testing, it was revealed that users encountered difficulties in completing specific tasks, especially in providing feedback on resolved complaints. There was also a high error rate in the login and complaint submission processes. Although government officials generally succeeded in completing their tasks, there were significant errors in the process. These findings indicate the need for further improvement, particularly in aspects not successfully addressed by users and the enhancement of efficiency in the complaint submission process. The importance of iteration and application design improvement is emphasized to enhance the overall user experience. These improvements are expected to more effectively meet user needs and increase satisfaction with the complaint service.